Understanding stickiness of sticky-cohesive foods - Kazemeini, Seyedmostafa (2024)
Stickiness is a textural characteristic of food that is a difficult area of research from both a human perception and instrumental measurement perspective. For this reason, different approaches were used in the present work to explore the challenges. Since the final stages of oral food processing lead to a sticky-cohesive texture, it was hypothesised that the sticky-cohesive texture would reach a certain level in all model foods of the present work.